Call Jane [videorecording (DVD)] - Schore, Hayley; Sethi, Roshan; Banks, Elizabeth, 1974-; Weaver, Sigourney, 1949-; Messina, Chris; Mara, Kate, 1983-; Mosaku, Wunmi; Smith, Cory Michael, 1986-; Edwards, Grace (Actor); Magaro, John, 1983- (Lionsgate, 2022)
Chicago, 1968. As the city and the nation are on the brink of political upheaval, suburban housewife Joy and her husband and daughter are living the all-American dream. But Joy's tranquil world is shattered when her life-threatening pregnancy forces her to navigate a medical establishment unwilling to help. This impossible situation leads Joy to the 'Janes,' an underground network providing the only available alternative, helmed by fierce advocates Virginia and Gwen, not only saving Joy's life but changing it forever.